Age‐Related Differences in Sensitivity to Facial Trustworthiness: Perceptual Representation and the Role of Emotional Development. Issue 5 (25th November 2019) - Baccolo, Elisa; Macchi Cassia, Viola
Abstract : The ability to discriminate social signals from faces is a fundamental component of human social interactions whose developmental origins are still debated. In this study, 5‐year‐old ( N = 29) and 7‐year‐old children ( N = 31) and adults ( N = 34) made perceptual similarity and trustworthiness judgments on a set of female faces varying in level of expressed trustworthiness. All groups represented perceived similarity of the faces as a function of trustworthiness intensity, but such representation becomes more fine‐grained with development. Moreover, 5‐year‐olds' accuracy in choosing the more trustworthy face in a pair varied as a function of children's score at the Test of Emotion Comprehension, suggesting that the ability to perform face‐to‐trait inferences is related to the development of emotional understanding.